Effects of Modified Board Game–Based Cognitive Stimulation on Cognitive Function in Community-Dwelling Older Adults: an Occupational Therapy Intervention Study - Aniek Puspitosari; Ninik Nurhidayah (Postgraduate, University of Mataram, 2026)
Cognitive decline is a common condition among older adults that may affect memory, attention, and functional independence. Non-pharmacological interventions, particularly activity-based approaches, are increasingly recommended to maintain cognitive function. Board game–based cognitive stimulation has emerged as a promising, engaging, and accessible intervention within occupational therapy practice. This study aimed to examine the effect of a modified board game–based cognitive stimulation program on cognitive function among community-dwelling older adults. This study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. A total of 50 pre-elderly and older adults were recruited using purposive sampling based on predetermined inclusion criteria. Cognitive function was measured using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) before and after the intervention. The intervention consisted of a modified board game program conducted over eight sessions, each lasting 30–60 minutes, integrating cognitive tasks across multiple domains. Data were analyzed using descriptive statistics and paired sample t-test with a significance level of p < 0.05. The findings showed a statistically significant improvement in cognitive function after the intervention (p = 0.000, p < 0.05). Participants demonstrated increased scores across multiple cognitive domains following the modified board game–based cognitive stimulation program. The modified board game–based intervention was effective in improving cognitive function among community-dwelling older adults. This approach offers a practical, low-cost, and engaging strategy that can be implemented in community and occupational therapy settings to support cognitive health and functional independence in aging populations.